Neurovascular Foramina of the Human Clavicle: Clinical Significance and diagnosis - Sreepreeti Champatyray; Sarthak Ranjan Nayak; Tapaswini Mishra; Saurjya Ranjan Das (Current Overview on Disease and Health Research Vol. 2, 2022)
The present study aims to determine the number, position, direction, of nutrient foramen and the foraminal index. The clavicle is a bone in the upper limb that distributes body weight to the axial skeleton. One nutrition foramen is usually situated on the shaft of the clavicle, away from the developing end, and permits the major nutrient artery to flow through. The vascularized clavicle is primarily used in joint allograft and bone grafting procedures. The current study was conducted on 62 clavicles of unidentified age and sex, out of them, 34 belong to right and 28 belong to left side. The bones were collected from the museum of Department of Anatomy and Forensic Medicine, IMS and SUM HOSPITAL, Bhubaneswar, India. The number, location and direction of nutrient foramina was documented and compared with the investigations done by the preceding authors. Mean foramen index was calculated by applying Hughes formula. Total 92 nutrient foramina were observed in 62 bones. Out of them single foramina was detected in 42 (67.74%) and double foramina in 12 (19.35%). More than 2 nutrient foramina were found in 8 (12.89%) clavicles. Location of the foramina was more common on posterior surface (76%) than on the inferior surface (24%). 65.21% of the foramina were present in middle 1/3rd of the clavicle. All are directed away from the growing end of the bones. Our study shows the average distance of the foramen from the sternal end was 67.9mm and the mean foramen index was 53.80. Conclusion: For vascularized bone grafts, internal fixation placement, and microsurgical vascularized bone transplantation, nutritional foramina must be recognized. During radiation therapy, it also maintains vascular supply. The study will also give an idea to the biomedical engineers for designing the clavicle bone model. Understanding of the nutrient foramina is also requisite to the vascularity during radiation therapy.